A moving story - Ferry, Beth; Lichtenheld, Tom (Harper, an imprint of HarperCollinsPublishers, 2024)
"With the utmost care, brothers and professional movers Tiny and Pete will move anything anywhere because they know that nothing is too small or too light to wrap up tight and treat just right. But during their biggest move yet, a young panda's pet turtle goes missing and even the brothers' efforts might not be enough to save the day"--